Power, productivity and profits - Frederick Guy; Peter Skott (University of Massachusetts, Department of Economics, 2007)
New information and communication technologies, we argue, have been 'power-biased': in many industries they have allowed firms to monitor workers more closely, thus reducing the power of these workers. An efficiency wage model shows that 'power-biased technical change' in this sense may generate rising inequality accompanied by an increase in both unemployment and work intensity.
Keywords: J31; O33; 330; power-biased technical change; efficiency wages; inequality; work intensity; Funktionelle Einkommensverteilung; Technischer Fortschritt; Qualifikation; Macht; Informationstechnik; Leistungsbeurteilung; Lohnstruktur; Theorie